The Role of (18) F-FDG PET/CT in Assessing Therapy Response in Cervix Cancer after Concurrent Chemoradiation Therapy - Choi, Jiyoun (Springer Berlin Heidelberg, 2013)
PURPOSE: To determine whether persisting cervical fluorodeoxyglucose (FDG) uptake after concurrent chemoradiotherapy (CCRT) for cervical cancer can reflect residual malignancy. METHODS: F-FDG PET/CT was performed before and after CCRT in 136 patients with cervical cancer. The maximum and mean standardized uptake values (SUVmax and SUVmean) were recorded from PET/CT scans performed pre- and post-treatment. SUVs were correlated with treatment response after CCRT. Final treatment response was determined by MRI and further follow-up PET/CT. One hundred four of 136 patients underwent pelvic MRI, and 32 of 136 patients underwent further follow-up PET/CT. Patients were classified into two categories: patients with residual tumor or patients without residual tumor (complete responder). Pre- and post-treatment serum squamous cell carcinoma antigen (SCC) levels were also recorded for comparison. The optimal cutoff value of SUVmax for predicting residual cervical tumor was determined using receiver-operating characteristic (ROC) analysis. RESULTS: Of 136 patients, 124 showed complete response on further follow-up studies and 12 were confirmed to have residual tumor. The post-treatment SUVmax and pre-/post-treatment SUVmean of complete responders were significantly lower than those of patients with residual tumor: 2.5 ± 0.8 and 7.2 ± 4.2/1.9 ± 0.7 for complete responders and 5.7 ± 2.6 and 12.8 ± 6.9/3.7 ± 0.7 for patients with residual tumor (p < 0.05). The pre-treatment SUVmax and pre-/post-treatment serum SCC levels of the complete responders tended to be lower than those of patients with residual tumor, but this did not have statistical significance. Using ROC analysis, an optimal cutoff SUVmax of 4.0 on the post-treatment PET/CT yielded a sensitivity, specificity, positive predictive value, and negative predictive value of 92 %, 94 %, 61 %, and 99 %, respectively (p < 0.001). CONCLUSIONS: Persistent cervical FDG uptake in(18)F-FDG PET/CT after CCRT for cervical cancer may be caused by residual tumor or post-therapy inflammation. A higher cutoff SUVmax than conventional criteria for cervical cancer in post-CCRT PET/CT might help to detect residual tumor.